Room Temperature Synthesis and Characterizations of ZIF-8 Formation at Water-Fatty Alcohols Interface - Misran H.; Mahadi N.; Othman S.Z.; Lockman Z.; Amin N.; Matsumoto A. (Institute of Physics Publishing, 2023)
Alcohols; Crystalline materials; Liquefied gases; Metal ions; Metals; Organometallics; Palm oil; Solvents; Surface active agents; Commercial surfactants; Hazardous solvents; Hydrothermal methods; Insoluble monolayer; Metal organic framework; Methylimidazole; Rhombic dodecahedron; Room temperature synthesis; Phase interfaces